HTML 4 for Dummies 5th Edition - Tittel, Ed (Wiley Publishing, 2011)
This book keeps the technobabble to a minimum and sticks with plain English whenever possible. Besides plain talk about hypertext, (X)HTML, and the Web, we include lots of examples, plus tag-by-tag instructions to help you build your very own Web pages with minimum muss and fuss. We also provide more examples about what to do with your Web pages after they’re created so you can share them with the world. We also explain the differences between HTML 4 and XHTML